Effects of high versus standard essential amino acid intakes on whole-body protein turnover and mixed muscle protein synthesis during energy deficit: A randomized, crossover study. Issue 3 (March 2021) - Gwin, Jess A.; Church, David D.; Hatch-McChesney, Adrienne; Howard, Emily E.; Carrigan, Christopher T.; Murphy, Nancy E.; Wilson, Marques A.; Margolis, Lee M.; Carbone, John W.; Wolfe, Robert R.; Ferrando, Arny A.; Pasiakos, Stefan M.
Summary: Background & aims: Consuming 0.10–0.14 g essential amino acids (EAA)/kg/dose (0.25–0.30 g protein/kg/dose) maximally stimulates muscle protein synthesis (MPS) during energy balance. Whether consuming EAA beyond that amount enhances MPS and whole-body anabolism following energy deficit is unknown. The aims of this study were to determine the effects of standard and high EAA ingestion on mixed MPS and whole-body protein turnover following energy deficit. Design: Nineteen males (mean ± SD; 23 ± 5 y; 25.4 ± 2.7 kg/m 2 ) completed a randomized, double-blind crossover study consisting of two, 5-d energy deficits (−30 ± 4% of total energy requirements), separated by 14-d. Following each energy deficit, mixed MPS and whole-body protein synthesis (PS), breakdown (PB), and net balance (NET) were determined at rest and post-resistance exercise (RE) using primed, constant L-[ 2 H5 ]-phenylalanine and L-[ 2 H2 ]-tyrosine infusions. Beverages providing standard (0.1 g/kg, 7.87 ± 0.87 g) or high (0.3 g/kg, 23.5 ± 2.54 g) EAA were consumed post-RE. Circulating EAA were measured. Results: Postabsorptive mixed MPS (%/h) at rest was not different ( P = 0.67) between treatments. Independent of EAA, postprandial mixed MPS at rest (standard EAA, 0.055 ± 0.01; high EAA, 0.061 ± 0.02) and post-RE (standard EAA, 0.055 ± 0.01; high EAA, 0.065 ± 0.02) were greater than postabsorptive mixed MPS at rest ( P = 0.02 and P = 0.01, respectively). Change in (Δ postabsorptive) whole-body (g/180 min) PS and PB was greater for high than standard EAA [mean treatment difference (95% CI), 3.4 (2.3, 4.4); P = 0.001 and −15.6 (−17.8, −13.5); P = 0.001, respectively]. NET was more positive for high than standard EAA [19.0 (17.3, 20.7); P = 0.001]. EAA concentrations were greater in high than standard EAA ( P = 0.001). Conclusions: These data demonstrate that high compared to standard EAA ingestion enhances whole-body protein status during underfeeding. However, the effects of consuming high and standard EAA on mixed MPS are the same during energy deficit. Clinical trial registry: NCT03372928, https://clinicaltrials.gov .